The commentary to some motifs of Peter Faltin's semiotics of music - Fujak, Julius (Interdisciplinary Studies in Musicology, 2018)
The article is focused on original musical semiotics of well known Slovak theoretician Peter Faltin (1939-1981), especially on his original semiotic theories in 1970s, including his last (unfinished) work Signification of Aesthetic Signs Music and Language based on L. Wittgenstein's philosophy. The paper also delas with studies of contemporary representatives of Slovak and Czech semiotics, aesthetics and postmodern philosophy such as Eubomir Chalupka, Jarmila Doubravovâ, Klement Mitterpach and Jûlius Fujak, who commented, explained and developed Faltin's thoughts in the frame of their research.